Visual communication : more than meets the eye - Jamieson, Harry, ....- (Bristol : Intellect Books, 2007)
We exist in a visual culture. The importance of reading and interpreting signs has become a rapidly increasing concern in recent years. This book offers an intricate theoretical perspective regarding the study of visual communication and expands the academic arena for debate concerning the visual. Veering away from normative approaches, the author advances with original strides into new ways of understanding the visual experience. Departing from aesthetic and graphic-based directions, the book employs information and language theory to support an enquiry into the connection between perception and linguistics. In dealing with ideas, rather than solutions, the book resonates with a philosophical tenor. However, the author is effective in providing a practical basis for many of the issues discussed alongside this theoretical stance. This book is targeted at a wide range of interdisciplinary readers including media, cultural and communication studies and particularly those with interests in visual theory.
Includes bibliographical references and index.
Keywords: Visual communication; Communicatie -- Visuele communicatie